STUDI LITERATUR PENGARUH PENERAPAN MANAJEMEN RISIKO TERHADAP BISNIS UMKM DI INDONESIA - Ridho Feriyanly; Arsyadona Arsyadona; Ryan Rauzan; Mhd Habbil Frizky; Tegar Achmad Faiq (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The implementation of risk management in MSMEs (Micro, Small, and Medium Enterprises) has become crucial in ensuring business continuity and stability, especially in developing countries like Indonesia. MSMEs play a vital role in national economic growth but are vulnerable to various internal and external risks. This study aims to analyze the impact of risk management practices on the success and sustainability of MSMEs in Indonesia. The research utilizes a Literature Review method, examining six prior studies relevant to the topic of risk management in MSMEs. Based on the analysis, it was found that effective risk management positively impacts loss reduction and enhances business stability for MSMEs. Through sound risk management, MSMEs can navigate uncertainties, maintain productivity, and optimize their resources. This indicates that risk management not only protects business assets but also strengthens the position of MSMEs amid dynamic economic competition. The study emphasizes that strategic risk management is a supporting factor forMSME success in achieving sustainable growth.